Superglue self-insertion an unusual case of foreign body into the male urethra - A case report - Mohsen Khalili-Fomeshi; Forough Ebrahimtabar; Mohammad Reza Aghagani; Parvaneh Mirabi; Mohammad Darzi (Babol University of Medical Sciences, 2020)
Background: Foreign body insertion in the urethra and bladder are relatively rare. These patients usually insert foreign body in urethra for eroticism, inquisitiveness, or as a consequence of disinhibited or disturbed behavior. Case presentation: Herein, we report a case of 41-year-old man presented with weak stream and suprapubic pain. Due to incontinence, he instilled superglue into his urethra. On perineal examination, a foreign body was palpable in the penile urethra. A 10 cm dried superglue block got out with incision at glance. Conclusion: Urethral foreign bodies are mostly found on physical examination and clinical history. Although imaging modalities are commonly used for FBs detection, the necessity of imaging modalities are still a controversy.